The waves - Woolf, Virginia, 1882-1941.; Herbert, Michael, 1949-; Sellers, Susan; Blyth, Ian.; Cambridge University Press (Cambridge, UK ; New York : Cambridge University Press, 2011)
"The Waves is one of the greatest achievements in modern literature. Commonly considered the most important, challenging and ravishingly poetic of Virginia Woolf's novels, it was in her own estimation 'the most complex and difficult of all my books'. This edition will be the most authoritative, most fully collated and annotated text available to scholars to date, and for considerable time to come. It maps the text of The Waves from the first British edition to all other editions published in Woolf's lifetime, as well as to all extant proofs. The text is presented in clearly readable form, with page-by-page direction to emendation, variants, and notes. The substantial introduction includes a detailed account of the novel's composition, publication and early critical reception. There are extensive explanatory notes on the text, a full chronology of composition and publication and a more general chronology covering Woolf's life and works"--
-- General editors' preface -- Notes on the edition -- Acknowledgements -- Chronology of Virgina Woolf's life and work -- List of archival sources for manuscript, typescript and proof material relating to The Waves -- Introduction -- Chronology of the composition of The Waves -- The Waves -- Explanatory notes -- Textual apparatus -- Textual notes.
Includes bibliographical references (pages 439-456)
Keywords: Identity (Psychology) -- Fiction; Friendship -- Fiction